When a Fly Ball Is Out of Reach: Catchability Judgments Are Not Based on Optical Acceleration Cancelation - Postma, Dees B. W.; Smith, Joanne; Pepping, Gert-Jan; van Andel, Steven; Zaal, Frank T. J. M. (Frontiers in Psychology, 2017)
The Optical Acceleration Cancellation (OAC) strategy, based on Chapman’s (1968) analysis of the outfielder problem, has been the dominant account for the control of running to intercept fly balls approaching head on. According to the OAC strategy, outfielders will arrive at the interception location just in time to catch the ball when they keep optical acceleration zero. However, the affordance aspect of this task, that is, whether or not an approaching fly ball is catchable, is not part of this account. The present contribution examines whether the scope of the OAC strategy can be extended to also include the affordance aspect of running to catch a fly ball. This is done by considering a fielder’s action boundaries (i.e. maximum running velocity and –acceleration) in the context of the OAC strategy. From this, only when running velocity is maximal and optical acceleration is nonzero, a fielder would use OAC to perceive a fly ball as uncatchable. The present contribution puts this hypothesis to the test. Participants were required to try to intercept fly balls projected along their sagittal plane. Some fly balls were catchable whereas others were not. Participants were required to catch as many fly balls as possible and to call ‘no’ when they perceived a fly ball to be uncatchable. Participants’ running velocity and –acceleration at the moment of calling ‘no’ were examined. Results showed that participants’ running velocity was submaximal before or while calling ‘no’. Also running acceleration was often submaximal. These results cannot be explained by the use of optical acceleration cancellation in judging catchability and ultimately call for a new strategy of locomotor control in running to catch a fly ball.